2018
DOI: 10.1007/s00018-018-2976-8
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory function of human IgA

Abstract: The prevailing concept regarding the immunological function of immunoglobulin A (IgA) is that it binds to and neutralizes pathogens to prevent infection at mucosal sites of the body. However, recently, it has become clear that in humans IgA is also able to actively contribute to the initiation of inflammation, both at mucosal and non-mucosal sites. This additional function of IgA is initiated by the formation of immune complexes, which trigger Fc alpha Receptor I (FcαRI) to synergize with various other recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 147 publications
0
90
0
Order By: Relevance
“…In general, the main antibody isotype at mucosal sites is considered to be IgA, while IgG is the main isotype in blood and tissue fluids. 20,23,24 However, this 'division of labor' by the different isotypes is unlikely to be black and white, considering the high concentrations of IgA in serum on one hand, and the levels of IgG in mucosal tissues on the other hand. Indeed, it has recently been shown that IgA in serum is important for shaping anti-bacterial responses in tissues such as blood, skin, and liver.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the main antibody isotype at mucosal sites is considered to be IgA, while IgG is the main isotype in blood and tissue fluids. 20,23,24 However, this 'division of labor' by the different isotypes is unlikely to be black and white, considering the high concentrations of IgA in serum on one hand, and the levels of IgG in mucosal tissues on the other hand. Indeed, it has recently been shown that IgA in serum is important for shaping anti-bacterial responses in tissues such as blood, skin, and liver.…”
Section: Discussionmentioning
confidence: 99%
“…The monomeric form and the lack of the secretory component enable serum IgA to bind to Fcαreceptor I (FcαRI) expressed by myeloid cells, such as monocytes, neutrophils, and some subsets of macrophages and dendritic cells (DCs) 3 . Serum IgA can thereby induce pro-inflammatory responses, such as the release of cytokines and chemokines, phagocytosis, degranulation, and formation of neutrophil extracellular traps (NETs) 4 . Opsonization of gut bacteria with IgA even converts anti-inflammatory intestinal CD103 + DCs to a proinflammatory phenotype, which protects against invading pathogens, but might also result in chronic inflammation 5 .…”
mentioning
confidence: 99%
“…The IgA is an abundant isotype in blood serum, in which it is normally present in concentrations of 1 to 3 mg/ml. In circulation, IgA is generally found as a monomer IgA [13,14]. Dimeric IgA is the predominant antibody in secretions of the gastrointestinal tract.…”
Section: General Features Of the Colon Mucosal: Barriers Of Protectiomentioning
confidence: 99%
“…In patients with IBD, the damage of the barrier function of the intestinal epithelial layer results in an influx of IgA-opsonized bacteria. Interestingly, it has been demonstrated that the presence of these immune IgA complexes in the lamina propria contributes to inflammation induced by FcαRI [13]. Recent findings have demonstrated that co-stimulation of FcαRI strongly affects pro-inflammatory cytokine production by some immune system cells such as phagocytes.…”
Section: General Features Of the Colon Mucosal: Barriers Of Protectiomentioning
confidence: 99%